Confirmatory factor analysis of the Frommelt Attitude Toward Care of the Dying Scale (FATCOD–B) among Italian medical students. Issue 5 (October 2015) - Leombruni, Paolo; Loera, Barbara; Miniotti, Marco; Zizzi, Francesca; Castelli, Lorys; Torta, Riccardo
Abstract: Objective: A steady increase in the number of patients requiring end-of-life care has been observed during the last decades. The assessment of healthcare students' attitudes toward end-of-life care is an important step in their curriculum, as it provides information about their disposition to practice palliative medicine. The Frommelt Attitude Toward Care of the Dying Scale (FATCOD–B) was developed to detect such a disposition, but its psychometric properties are yet to be clearly defined. Method: A convenience sample of 608 second-year medical students participated in our study in the 2012/2013 and 2013/2014 academic years. All participants completed the FATCOD–B. The sample was randomly divided in two subsamples. In the item analysis, reliability (Cronbach's α), internal consistency (item–total correlations), and an exploratory factor analysis (EFA) were conducted using the first subsample ( n = 300). Using the second subsample ( n = 308), confirmatory factor analysis (CFA) was performed using the robust ML method in the Lisrel program. Results: Reliability for all items was 0.699. Item–total correlations, ranging from 0.03 to 0.39, were weak. EFA identified a two-dimensional orthogonal solution, explaining 20% of total variance. CFA upheld the two-dimensional model, but the loadings on the dimensions and their respective indicators were weak and equal to zero for certain items. Significance of Results: The findings of the present study suggest that the FATCOD–B measures a two-dimensional construct and that several items seem in need of revision. Future research oriented toward building a revised version of the scale should pay attention to item ambiguity and take particular care to distinguish among items that concern emotions and beliefs related to end-of-life care, as well as their subjects (e.g., the healthcare provider, the patient, his family).